3D morphological analysis of composite materials with aggregates of spherical inclusions - Delarue, Arnaud (Image analysis and stereology, 2003)
Composite materials containing aggregates of spherical inclusions are studied from 3D images obtained by X-ray microtomography. Using two point statistics in different directions, and the empirical distribution of orientations of pairs of inclusions, interesting details concerning the anisotropy of the distribution of inclusions are obtained and are related to the method of construction for these materials. Some 3D morphological properties, available on the 3D images, give new information on the shape and the distribution of aggregates: tortuosity of shortest paths in the matrix, local volume fraction,geodesic distance function, local histograms of numbers of objects.
Keywords: Materiali, testiranje; Materials Testing; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Probability; Verjetnost; morfologija; kompoziti; stereologija